«Bribe» or «Undue Advantage»: Linguistic Aspects of the Formation of Legal Terminology - Dotsenko, Olena (Studia Philologica, 2024)
The article analyses the consequences of the lack of a comprehensive linguistic examination of legal drafts on the quality of the language design of legal acts in Ukraine and examines examples of unsuccessful interpretation by lawyers of the language design of legal acts. The experience of the expert activity of the Ukrainian Commission on Legal Terminology, whose specialists carried out a thorough terminological and linguistic examination of the draft of the current Constitution of Ukraine and some regulations, is described and the need for the formation of a similar unit within the Apparatus of the Verkhovna Rada of Ukraine is noted. The linguistic interpretation of the expediency of changing the definition of "bribe" with the term "undue benefit" proposed in the article proves that ignoring qualitative linguistic expertise has a negative effect on the language design of legal norms. In particular, it was established that the translations of international anti-corruption documents, which became the basis for changing the terms, contain a number of contradictions caused by the use of multilingual texts as primary sources, as well as the lack of systematic linguistic processing of the terminological apparatus of the anti-corruption field of criminal law and the failure to take into account the features of the structure of the term and the linguistic design of its components. The violation of the norms of codification of legal terminology in the Criminal Code of Ukraine, in particular the provision of several identical but linguistically different definitions of the concept of "undue benefit" and the violation of the lexical norms of the modern Ukrainian literary language in the formulation of such definitions have been demonstrated. The specifics of the use of the synonym’s "bribe" and "undue benefit" in texts of different styles were analysed based on the materials of the General Regionally Annotated Corpus of Ukrainian.